2000
DOI: 10.1103/physrevb.62.361
|View full text |Cite
|
Sign up to set email alerts
|

Random field and random anisotropy effects in defect-free three-dimensionalXYmodels

Abstract: Monte Carlo simulations have been used to study a vortex-free XY ferromagnet with a random field or a random anisotropy on simple cubic lattices. In the random field case, which can be related to a charge-density wave pinned by random point defects, it is found that long-range order is destroyed even for weak randomness. In the random anisotropy case, which can be related to a randomly pinned spin-density wave, the long-range order is not destroyed and the correlation length is finite. In both cases there are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Moreover, another Monte Carlo study of the RAM with m = 2 and the same relation between J and D obtained critical exponents with values similar to the XY -ferromagnetic transition, except that the heat capacity critical exponent was found to be positive [68]. It was shown that the long-range order is not destroyed in the vortex-free model with p−fold fields [67].…”
Section: Monte Carlo Simulationsmentioning
confidence: 79%
“…Moreover, another Monte Carlo study of the RAM with m = 2 and the same relation between J and D obtained critical exponents with values similar to the XY -ferromagnetic transition, except that the heat capacity critical exponent was found to be positive [68]. It was shown that the long-range order is not destroyed in the vortex-free model with p−fold fields [67].…”
Section: Monte Carlo Simulationsmentioning
confidence: 79%
“…[13] The same concept was applied to other systems, such as superfluid 3He-A in aerogel. [14] There has also been analytical work accompanied by Monte Carlo studies on small lattices [15,16,17,18] which assumed thermal equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…The FM order, which grows at higher temperatures, vanishes because of a random field effect [11]. Later, it was pointed out that not random field but random anisotropy brings a RSG-like phenomenon [12,13]. In a FM model with random anisotropy, as the temperature is decreased from a high temperature, there first appears a correlated SG (CSG) phase that is characterized by a well developed FM spin correlation.…”
mentioning
confidence: 99%